Article 151 of The Criminal Code of Ukraine: the challenges of legislative determination and correlation of the objective criterions of the corpus delicti (Law and Safety, 2020)
A number of issues related to the criminal and legal norm on liability for illegal placement in a psychiatric institution have been analyzed – the Article 151 of the current Criminal Code of Ukraine. The author has researched the way how the name of the specified crime and its legal content was defined by the legislation.The substantive part of the article begins with a brief overview of general theoretical provisions about the object and the objective aspect of the crime and the conclusions about the need for some consent between these features. Then a direct analysis of the Article 151 of the Criminal Code of Ukraine begins.Without denying in general the harmfulness of illegal placement in a psychiatric institution precisely for the will, honor and dignity of a man, it has been noted that today the norm of responsibility for such actions given its name and content is not the evidence of encroachment on these social values, despite the fact that it is the will, honor and dignity that are legally defined as the generic object of the crime. Particular attention has been paid both to the absence of appropriate features in the norm that would determine the involuntary behavior, and features that determine the encroachment on dignity or honor.One of the reasons for this situation is the fact that the legislator ignored the terminology of special legislation, which is the Law of Ukraine on “Psychiatric Care”, despite the fact that the Article 151 of the Criminal Code of Ukraine is a blanket norm. According to the author, it is expedient to include the professional definitions set forth in the special legislation into the content of criminal and legal norm to determine both the features of the objective aspect of the crime and the victim. Legislative use of the phrase “mentally healthy person” instead of the professional definition of “person without a mental disorder” and the concept of “accommodation” instead of the professional word “hospitalization” have been criticized.Particular attention has been paid to the absence of a direct indication in Article 151 of the Criminal Code of Ukraine of the illegality of keeping the victim in a psychiatric institution as an independent feature of a socially dangerous act. The author has noted on doubtfulness of the content of the sanction of the part of the considered Article in view of the content of responsibility for illegal imprisonment as a crime of a certain kind. The author’s wording of the criminal and legal norm of the Article 151 of the Criminal Code of Ukraine has been offered, in particular, changes to the title of the Article and the disposition of its first part.
Keywords: illegal placement to a mental hospital; hospitalization; a person who has a mental disorder; psychiatric care facility; psychiatric stationery